Innovation of air quality detector in passenger car using IoT - Farih Bin Deraman; Asrudin Bin Mat Ali; Normi Bin Muhamad (Indonesian Institute For Counseling, Education and Therapy, 2020)
The internet of things (IoT), is a system of interrelated computing devices, mechanical and digital machines, objects, animals or people that are provided with the ability to transfer data over a network without requiring human-to-human or human-to-computer interaction (Gismalla Abdullah, 2017). The internet of things helps people live and work smarter as well as gain complete control over their lives. A passenger car is a road motor vehicle, intended for the carriage of passengers and designed to seat no more than nine persons. The problems occur in passenger car when there is no device that monitor the quality of air in the car’s cabins. Air Quality Detector is an automatic system that being developed to send the value of Carbon Dioxide (CO2) level in car to LCD display and Blynk App. The existing low-end car do not have any system that can notify the passengers regarding the CO2 level in the car. As a solution, this innovation able to detect exact condition of carbon dioxide level in car to the LCD display and Blynk app to be warned by the passenger. Air Quality Detector has been simulated to run successfully in term of controlling and monitoring CO2 in the car.